# Solve for y -3/4y=9/16

-34y=916
Multiply both sides of the equation by -43.
-43⋅(-34)⋅y=-43⋅916
Simplify both sides of the equation.
Simplify -43⋅(-34)⋅y.
Cancel the common factor of 4.
Move the leading negative in -43 into the numerator.
-43⋅(-34)⋅y=-43⋅916
Move the leading negative in -34 into the numerator.
-43⋅-34⋅y=-43⋅916
Factor 4 out of -4.
4(-1)3⋅-34⋅y=-43⋅916
Cancel the common factor.
4⋅-13⋅-34⋅y=-43⋅916
Rewrite the expression.
-13⋅-3⋅y=-43⋅916
-13⋅-3⋅y=-43⋅916
Cancel the common factor of 3.
Factor 3 out of -3.
-13⋅(3(-1))⋅y=-43⋅916
Cancel the common factor.
-13⋅(3⋅-1)⋅y=-43⋅916
Rewrite the expression.
-1⋅-1⋅y=-43⋅916
-1⋅-1⋅y=-43⋅916
Multiply.
Multiply -1 by -1.
1⋅y=-43⋅916
Multiply y by 1.
y=-43⋅916
y=-43⋅916
y=-43⋅916
Simplify -43⋅916.
Cancel the common factor of 4.
Move the leading negative in -43 into the numerator.
y=-43⋅916
Factor 4 out of -4.
y=4(-1)3⋅916
Factor 4 out of 16.
y=4⋅-13⋅94⋅4
Cancel the common factor.
y=4⋅-13⋅94⋅4
Rewrite the expression.
y=-13⋅94
y=-13⋅94
Cancel the common factor of 3.
Factor 3 out of 9.
y=-13⋅3(3)4
Cancel the common factor.
y=-13⋅3⋅34
Rewrite the expression.
y=-1⋅34
y=-1⋅34
Rewrite -1(34) as -(34).
y=-34
y=-34
y=-34
The result can be shown in multiple forms.
Exact Form:
y=-34
Decimal Form:
y=-0.75
Solve for y -3/4y=9/16

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top